Validity and Reliability of Physics Learning Devices Based on Guided Inquiry to Improve Students' Creative Thinking Skills - Fikri Akbar; Ni Nyoman Sri Putu Verawati; Wahyudi (Postgraduate Program, University of Mataram, 2025)
This study aims to develop guided inquiry-based physics learning devices to enhance students’ creative thinking skills. The development model used is the 4D model (Define, Design, Develop, and Disseminate) developed by Thiagarajan, Semmel, and Semmel. The learning devices developed include teaching modules, learning materials, student worksheets (LKPD), and evaluation instruments. The validity and reliability of the devices were analyzed through assessments by six validators, consisting of three expert lecturers and three practicing teachers. The validation results indicated that all developed learning devices fall into the